Earnings Mobility in Times of Growth and Decline : Argentina from 1996 to 2003 - Fields, Gary S. (2012)
In recent years Argentina's economy has experienced both rapid growth and severe decline. In this paper, we use a series of one-year long panels to study who gained the most in pesos when the economy grew and who lost the most in pesos when the economy contracted. Various considerations led us to expect that mobility would be divergent--that is, that the individuals who started with the highest initial earnings would enjoy the largest earnings gains in pesos. Contrary to expectations and for a wide range of specifications, mobility is found to be mostly convergent, sometimes neutral, and never divergent.